2009
DOI: 10.1182/blood-2008-03-146084
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced thrombocytosis in transgenic mice expressing reduced levels of Mpl in platelets and terminally differentiated megakaryocytes

Abstract: We generated mice expressing a fulllength Mpl transgene under the control of a 2-kb Mpl promoter in an Mpl Ϫ/Ϫ background, effectively obtaining mice that express full-length Mpl in the absence of other Mpl isoforms. These mice developed thrombocytosis with platelet levels approximately 5-fold higher than wildtype controls and markedly increased megakaryocyte numbers. The reintroduction of one wild-type Mpl allele restored normal platelet counts. We excluded the deletion of Mpl-tr, a dominant-negative isoform,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
62
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 56 publications
(66 reference statements)
5
62
1
Order By: Relevance
“…According to this model, every event leading to a decrease in MPL or JAK2 expression or in signaling intensity may extend the proliferative stage and might induce an amplification of the progenitor cell compartment in MPNs. Accordingly, a thrombocytosis is observed in transgenic mice expressing reduced levels of MPL, 29,30 and a decrease in MPL expression was observed in platelets and MKs of patients with MPNs, with either PMF or ET. [13][14][15] This decrease in MPL expression was obvious in patients harboring a JAK2 V617F or a MPL W515 mutation, whereas MPL expression was increased in ET patients without any of these mutations.…”
Section: Discussionmentioning
confidence: 99%
“…According to this model, every event leading to a decrease in MPL or JAK2 expression or in signaling intensity may extend the proliferative stage and might induce an amplification of the progenitor cell compartment in MPNs. Accordingly, a thrombocytosis is observed in transgenic mice expressing reduced levels of MPL, 29,30 and a decrease in MPL expression was observed in platelets and MKs of patients with MPNs, with either PMF or ET. [13][14][15] This decrease in MPL expression was obvious in patients harboring a JAK2 V617F or a MPL W515 mutation, whereas MPL expression was increased in ET patients without any of these mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Tiedt et al recently found that mpl mRNA expression directed by the same 2-kb promoter decreased over the course of megakaryocyte maturation. 39 Thus, the apparent differences in the restoration of mpl mRNA expression between the 2 hematopoietic compartments may have been significantly influenced by the maturation state of the megakaryocyte progenitors we studied.…”
Section: Discussionmentioning
confidence: 99%
“…The platelet counts were overcorrected, a finding also reported by another group that used an Mpl transgenic expression vector with the same 2-kb promoter to rescue the mpl Ϫ/Ϫ mouse. 39 In contrast, the stem cell-repopulating ability of the marrow compartment in There are 2 possible causes for the thrombocytosis seen in the transgene-rescued mice: (1) an inherent defect in function of the transgenic Mpl receptor leading to excessive megakaryocyte lineage proliferation or (2) dysregulation of TPO homeostasis. Excessive signal transduction from the transgenic Mpl receptor would raise concerns about an increased risk for the development of a myeloproliferative disorder.…”
Section: Discussionmentioning
confidence: 99%
“…In normal individuals, this model describes an effective feedback system to regulate TPO-driven megakaryocyte and platelet production according to need. The reciprocal relationship between platelet number and circulating TPO level is clearly evident in bone marrow transplant patients (1), and the key role of the TPO receptor is illustrated by the elevated circulating TPO in Mpl −/− mice (3) and the modest elevation of platelet counts in transgenic mice expressing low levels of Mpl (4,5). However, the relationship between circulating TPO concentration and peripheral platelet counts is not always conserved in pathological states of thrombocytosis and thrombocytopenia (6)(7)(8)(9), suggesting that a simple relationship among megakaryocyte and platelet Mpl mass, circulating TPO concentration, and the degree of stimulation of megakaryopoiesis may not always hold.…”
Section: Pf4cre/pf4crementioning
confidence: 99%